Selegiline Alleviates the Depressive-Like Behaviors of Methamphetamine Withdrawal Syndrome Through Modulating Mitochondrial Function and Energy Hemostasis - Mir-Jamal Hosseini; Sima Askari Sadat-Mahaleh; Hamed Ghavimi (Tabriz University of Medical Sciences, 2022)
Background: Methamphetamine (METH) is considered the second most commonly abused drug in the world. There is limited or no evidence concerning the effective treatment of METH withdrawal symptoms, such as depression and anxiety. Mode of action of selegiline (increase of the brain neurotransmitter activity) suggests that it might be useful in METH withdrawal syndrome treatment, being capable of diminishing the preference and depression involved in drug degeneration and addictive activities. Methods: Mice were randomly divided into 10 groups (n= 10): five METH-nondependent groups treated with normal saline intraperitoneal (i.p) for two weeks, to which, from the 15th day, selegiline (10, 20 and 40 mg/kg; i.p) or fluoxetine (5 mg/kg; i.p) was administrated for 10 consecutive days. Other groups injected METH (2 mg/kg, at 12-h intervals) for 14 days. From the 15th day, the 10-day period of METH abstinence started and the above-mentioned doses of selegiline or fluoxetine were injected. Then, the mice were evaluated for depression and biochemical assessments from the 25th day of the study. Results: The data indicated that post-treatment with selegiline (10-40 mg/kg; i.p) for 10 days reversed METH-induced depressive-like behaviors in the forced swimming test (FST), tail suspension test (TST), and splash test with exerting no effects on the locomotor activity. Furthermore, none of the previously proposed treatments affected the behavioral abnormality in the control animals. Moreover, both selegiline and fluoxetine as standard antidepressant drug, substantially improved the levels of mitochondrial reduced glutathione (GSH), malondialdehyde (MDA), and adenosine triphosphate (ATP). Conclusion: Our findings demonstrated that selegiline produced antidepressant-like effects following METH withdrawal and prevented the mitochondrial dysfunction in the male mice.